Comparative Study of Hardfacing of AISI 1020 Steel by Three Different Welding Processes (Global Journals of Research in Engineering, 2013)
Hard facing by welding techniques are used mainly to improve the service life of machine parts either by rebuilding or by fabricating in such a way as to produce a metallic/alloy wall section to withstand the problems of wear, erosion, corrosion, etc. An attempt has been made in this paper, to determine a better welding process to weld hard face AISI 1020 steel based on wear analysis. In the present paper three different welding processes are compared. Based on the study, the specimens prepared using TIG welding process yielded better wear properties compared to the specimens prepared using Gas welding and Arc welding processes until certain sliding velocities. The Gas welding and Arc welding processes yielded better wear properties for still higher range of sliding velocities. The factors contributing to achieve the said results were interpreted.
Keywords: AISI 1020 steel; hardsur facing; gas welding; arc welding; TIG welding; wear property